Rational Preference in Habitual Interactions - Yustinus Suhardi Ruman (Bina Nusantara University, 2016)
Article focused on human being as a rational creature. Therefore, every undertaken preference could be interpreted as a rational selection. The issue emerged will clarify whether every human action can be categorized as a rational act. This article aimed to clarify the conditions that could be considered as the fundamental for appraising a choice as a rational choice. The method utilized to explicate the subject was literature review. There are several conditions that were discussed in this article, they were the principle of rationality, preferences, interests, and beliefs. The research finds out that the fourth condition is the basis for a rational choice.